2012
DOI: 10.1200/jco.2012.30.27_suppl.35
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnostic value of survivin and its alternative splice variants in breast cancers.

Abstract: 35 Background: The inhibitor of apoptosis (IAP) protein Survivin and its splice variants are differentially expressed in breast cancer tissues and have recently been shown to be released from tumor cells via small membrane-bound vesicles called exosomes. Tumor-derived exosomes play multiple roles in tumor growth and metastasis and may produce these functions by impacting immune escape, tumor invasion and angiogenesis. We, therefore, hypothesize that analysis of exosomal Survivin and its splice variants may pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Additionally, the diverse expression pattern of exosomal Survivin-2B from the serum of patients with breast cancer may be used as a biomarker for patients with early breast cancer (Khan et al, 2012).…”
Section: Diagnostic Toolmentioning
confidence: 99%
“…Additionally, the diverse expression pattern of exosomal Survivin-2B from the serum of patients with breast cancer may be used as a biomarker for patients with early breast cancer (Khan et al, 2012).…”
Section: Diagnostic Toolmentioning
confidence: 99%
“…Emerging evidence has demonstrated the clinical utility of circulating EVs as a diagnostic, non-invasive biomarker in patients with malignant tumors. Several studies have demonstrated their potential in various cancers, including breast [ 26 , 27 , 28 , 29 ], prostate [ 30 , 31 ], pancreatic [ 32 ], ovarian [ 33 , 34 ], colorectal cancers [ 14 ], and glioblastoma [ 35 ] but the evidence is lacking in bone and soft-tissue sarcomas. In this study, we first demonstrate that circulating SS-derived EVs may represent a novel target for liquid biopsy of this aggressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of staining was scored semi-qualitatively as follows: 0, negative; 1, weak; 2, intermediate; and 3, strong. The final score was defined as the sum of both parameters (extension and intensity) and grouped as negative (score 0 and 2) and positive (score 3–6), as previously described [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“… 69 Survivin is a member of the apoptosis inhibitor family that is expressed at high levels in breast cancer and regulates cell division and apoptosis. 70 , 71 Breast cancer cells-activated CAFs release exosomes that promote proliferation, migration, colony formation, and EMT in MDA-MB-231 and MCF-7 breast cancer cells; however, these events are not induced by EVs from mammary non-tumorigenic epithelial cells HBL-100. Moreover, an in vivo model using BALB/c-NU mice shows that survivin induces overexpression of SOD1 in CAFs to promote proliferation and metastasis, whereas SOD1 expression is higher in breast cancer women stage II, III, and IV compared with breast cancer women stage I .…”
Section: Cafs-derived Evs Promote An Aggressive Phenotype In Mammary ...mentioning
confidence: 99%